Islam Nusantara in Slogan Bhinneka Tunggal Ika: Al-Quran Perspective - Rahma Fitria Purwaningsih; Doli Witro (Universitas Muhammadiyah Magelang, 2020)
Islam is a religion of peace. However, terrorism, bombings, and inter-religious conflicts affect this image, and Islam is being seen as a radical that cannot tolerate differences. It becomes ironic when Islam is seen as a radical religion in Indonesia which is considered as a pluralist and homogeneous state with the slogan Bhinneka Tunggal Ika. Also, the purpose of Islam Nusantara, which became popular recently in the slogan, has become questionable. This research reflects on how much radicalism has infected Indonesian society and injured cultural differences. It also discusses Islam Nusantara in ‘Bhinneka Tunggal Ika’, in relation to the pros and cons of differences as well as the value of unity in cultural diversity. A comprehensive literature study and a qualitative approach was used in this research. The study shows that the controversy over the archipelago Islam is as a result of the definition of terms. Furthermore, Islam Nusantara is interpreted as a common ground Islam and is not a new understanding, manhaj, or a paradigm that is synonymous with violence or forceful Islamization of the region.